Neutralizing potential of Rauvolfia serpentina root extract against Naja naja venom - Thulasi Sivaraman; Nadooparambil Sasi Sreedevi; Subramani Meenachisundharam; Ramachandran Vadivelan (Universidade de São Paulo, 2020)
Snake bites are a serious health hazard occurs throughout the world especially in tropical countries like India. Anti-Snake Venom Serum is the only remedy available to treat snake bite victims successfully till date. Infusion of ASV may lead to adverse reactions ranging from severe itching of the skin, hives to potentially serious allergic reactions. Considering all above difficulties research workers all over the world is constantly in search of a cheap and readily available easy formulate remedy for treating snake bite victims. In present study aqueous extract of Rauvolfia serpentina root was checked for the antidote properties against Naja naja venom by in vitro and in vivo methods. Various in vitro neutralization tests like Acetyl cholinesterase, Protease and ATPase activity of Naja naja venom were carried out and the root extract was neutralized all the toxic effects induced by the venom. The in vivo assessment of venom lethality (LD50) of Naja naja venom was found to be 0.301 µg. The aqueous root extract was effectively neutralized the venom lethality and effective dose (ED50) was found to be 12.88 mg/ 3LD50 of Naja naja venom. LC-MS analysis from root extract of Rauvolfia serpentina was done for confirmation of the bioactive compounds.